2019
DOI: 10.1111/jpg.12742
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Quality Evolution of Upper Carboniferous (Westphalian) Tight Gas Sandstones, Lower Saxony Basin, Nw Germany

Abstract: This paper investigates reservoir quality development in tight Upper Carboniferous fluvial sandstones (Westphalian C/D) in the Lower Saxony Basin, NW Germany. The study integrates data from three outcrops (Piesberg, Woitzel and Hüggel) in the south of the basin with that from two wells (Wells A and B) located at gas fields approximately 50 km to the north. Petrographic and petrophysical data are related to the diagenetic evolution of the sandstones and the burial and structural history of the Lower Saxony Basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 70 publications
(165 reference statements)
1
17
0
Order By: Relevance
“…13b) would result in an even better correlation coefficient of R = 0.91. Overall, clay minerals are interpreted to be one of the main controls on a deterioration of reservoir quality, as they might retain porosity in form of microporosity but contribute to a loss of effective porosity, resulting in reduced permeabilities, which is in line with the results of previous studies (Becker et al 2019;Ehrenberg 1990;Gaupp and Okkerman 2011).…”
Section: Clay Minerals and Microporositysupporting
confidence: 86%
See 3 more Smart Citations
“…13b) would result in an even better correlation coefficient of R = 0.91. Overall, clay minerals are interpreted to be one of the main controls on a deterioration of reservoir quality, as they might retain porosity in form of microporosity but contribute to a loss of effective porosity, resulting in reduced permeabilities, which is in line with the results of previous studies (Becker et al 2019;Ehrenberg 1990;Gaupp and Okkerman 2011).…”
Section: Clay Minerals and Microporositysupporting
confidence: 86%
“…Recent outcrop analog studies also demonstrated heterogeneity in lateral permeability in Triassic Buntsandstein of up to two orders of magnitude in a single bed several meters apart (Schmidt et al 2020b). Upper Carboniferous sandstones also show lateral permeability variations by two orders of magnitude over 150 m lateral distance in a 3 m bed (Becker et al 2019(Becker et al , 2017. However, it is commonly assumed to not vary significantly in the lateral direction in reservoir modelling approaches (Cannon 2018;Gibbons et al 1993).…”
Section: Vertical Permeability Heterogeneitymentioning
confidence: 99%
See 2 more Smart Citations
“…Reservoir sandstones also compact mechanically and chemically over geological timescales affecting petrophysical and mechanical properties (Houseknecht 1987;Lundegard 1992). Their reservoir properties change during subsidence, and their diagenesis is related to initial composition and grain coatings (Aagaard et al 2000;Busch et al 2020;Monsees et al 2020), fluid type, chemistry and pressure (Bjørlykke and Høeg 1997;Gaupp et al 1993), thermal exposure over time at depth intervals (Becker et al 2019;Busch et al 2018;Lander et al 2008), and faults controlling temperature overprint by hydrothermal fluid circulation (Wüstefeld et al 2017). It is thus of crucial importance for assessing the rock's porosity and permeability, and its viability as a reservoir (Morad et al 2010;Worden et al 2018).…”
Section: Introductionmentioning
confidence: 99%